Creative (Critical) Discourse Analysis of Tiziano Ferro and Ricky Martin "Coming Out". (February 2014) - Rivera Santana, Carlos; Vélez Agosto, Nicole M.; Benozzo, Angelo; Colón De la Rosa, Samuel
In this article, we explore and problematize the coming out discourses of Ricky Martin and Tiziano Ferro's through a creative (critical) discourse analysis. We first contextualize the historicity of Ricky Martin and Tiziano Ferro's artistic careers and argue that their coming out process is a privileged laboratory to understand the ways strategies and tactics of discourses are deployed. Second, through a Critical Discourse Analysis and collaborative writing inquiry approach, we present a creative fictional dialogue to showcase our analysis. This can be called creative (critical) discourse analysis. Third, we further reflect and theorize about these coming out discourses using Queer Theory, Governability, and the concept of Glory and the Media as privileged spaces for power. This will lead us to question the centered subject or a solid identity, the manifestations of coming out discourses, and the role of Glory and the Media in the socialization process.